The design of Islamic worldview in preventing radicalism at the University of Muhammadiyah Gresik - Amirudin, Noor (ATTARBIYAH: Journal of Islamic Culture and Education, 2023)
This research is motivated by students who are not consistent in showing moderate thoughts. As happened to Islamic education students at the University of Muhammadiyah Gresik, some took part in extra-campus activities such as the student dakwah institute. Still, in their development, their understanding turned into acts of group and ideological struggle. So, it is necessary to have an Islamic mindset to control their religious knowledge so that it is dynamic and tolerant. To explore these problems, a research method with a qualitative approach is needed, which aims to understand specific issues related to complexity in depth. In contrast, researchers use a case study type of research. The result is the role of the Islamic worldview, which is carried out through the learning process of Islamic education in an andragogical way on campus, in the context of teaching and learning activities in Islamic education study programs, the creativity of lecturers professionally in the field of Islam who are qualified, including integrating actual themes designed to provide insight basic knowledge of Islam to students so that they have a robust Islamic framework of thought and are increasingly enthusiastic about exploring Islam more deeply, to stem the flow of radical opinions.